Influence of Structure on Optical Properties of WO3 Thin Films Deposited by Sputtering Method - Ngoc, Le Van; Thinh, Nguyen Duc; Tuan, Tran; Phuong, Duong Ai; Dat, Huynh Thanh (Communications in Physics, 2012)
In this paper we report the synthesis of WO_3 thin films and investigate the effect of the structure on their optical properties. The WO_3 thin films are coated on glass substrates from both W and WO_3 targets by the magnetron sputtering method in (Ar+O_2) plasma under different deposition temperatures, varying from room temperature to 480 C. We also evaluate the band gap energy of WO_3 by considering the transitions between the valence and the conduction bands. This result suggests that the best choices are diagonal and allowed transitions. Based on the values of band gap energy and XRD pattern, we indicate the relationship between crystalline order and optical property and consequently, the difference in color of the samples.